ANÁLISE DOS EFEITOS DA COOPERAÇÃO E DAS FONTES DE INFORMAÇÃO SOBRE A INOVAÇÃO DE PRODUTOS, PROCESSOS E MERCADO EM EMPRESAS DO ESTADO DE SÃO PAULO - OLIVEIRA, GLORIA MARIA MEROLA DE (2011)
In the strategy area, innovation is recognized as a possible source of competitive advantage in the medium and long term. In Brazil, where actions to improve the companies competitiveness have been taken, innovation is reflected as a matter of great interest among those who seek for an improvement in performance of its products and processes, and the conquest of new markets. We are not aware, however, of documents that present actual results in innovation coming from the adoption of strategic tools such as cooperation and access to sources of information. This work aims to contribute to the analysis of the impact noticed by the executives about the effects of cooperation and information sources on product innovation, process and market, considering companies based in São Paulo. We have used the database of PINTEC - Research on Technological Innovation, published by IBGE - Brazilian Institute of Geography and Statistics, for the triennium 2006-2008. We estimated 32 categorical multiple regression models in order to check how the variables cooperation and information sources explain the perceived impact on products, processes and markets. The regression results for 1413 companies indicate that, to a high cooperation with universities or research institutes it is possible to observe a highly significant impact on production capacity or the provision of services increasing and a significant impact in opening new markets. For all variables - product, process and market - highly significant results were observed of innovative impact when access to sources of information with clients, customers and suppliers at all levels of importance (high, medium and low) assigned by the respondent was obtained. Access to sources of information with universities and higher education institutions showed significance to: a) improvement in quality of goods or services, b) to expand the range of goods or services offered, c) reduction of production costs or services provided and d) the opening of new markets. For these same sources, very significant innovative impacts have been reported, as they allowed companies to maintain and / or expand the company's participation in the market. Among the main contributions of this work are academic knowledge and practical of innovative impacts through the executives’ perspective. It is expected that the results of this study to can base decisions of managers and policy makers to innovate.